Penyuluhan Pupuk Organik Cari Batang Pisang untuk Tanaman Kacang Panjang di Kelompok PKK Pasir Putih Kota Jambi - Hasriati Nasution; Emanauli; Yusfaneti (Studium: Jurnal Pengabdian Kepada Masyarakat, 2023)
Long bean (Vigna sinensis L) is a vegetable commodity widely cultivated in lowland areas. Its high nutritional content has made it popular among communities as a vegetable and salad ingredient. This study aims to enhance the knowledge and skills of the PKK group in cultivating long beans using liquid organic fertilizer made from banana stems. Based on surveys, long beans are consumed by households 2-3 times a week with specific preferences regarding their characteristics. The cultivation of long beans takes place in ultisol soil, which requires the application of fertilizer to improve fertility. Therefore, a 3-month program consisting of training and demonstrations on the production of liquid organic fertilizer from banana stems was conducted in the PKK RT 23 group in Pasir Putih Village, Jambi City. The community engagement program aimed to provide knowledge on the use of compost as organic fertilizer and the process of making liquid organic fertilizer from banana stems. The community engagement team provided the necessary materials and tools for the training and demonstrations. The utilization of liquid organic fertilizer is expected to enhance long bean harvests and overall increase the income of the PKK group.